O-022 A New Protocol for Anticoagulation with Tirofiban during Stenting of Intracranial Aneurysms. (26th July 2014) - Chalouhi, N; Zanaty, M; Starke, R; Jabbour, P; Hasan, D
Abstract : Introduction: Stenting techniques such as stent-assisted coiling and flow diversion are increasingly used for treatment of intracranial aneurysms. In previous reports, patients were pretreated were aspirin and clopidogrel prior to the intervention for prevention of thromboembolic complications. Prior studies also often rely on aspirin response and P2Y assessment, which often delays treatment in non-responders. The present study assesses the safety and efficacy of a new protocol for anticoagulation using tirofiban during stent-assisted coiling and flow diversion of intracranial aneurysms. Methods: In this prospective study, all patients received a 0.10 mcg/kg/min maintenance infusion of tirofiban intraoperatively without a loading dose. The infusion was started immediately after deployment of the stent or flow diverter and continued for 12 h following the procedure. No patient was pretreated with aspirin or clopidogrel. Data on procedural safety was prospectively collected. Results: A total of 128 aneurysms were treated with this protocol. Mean patient age was 56.2 years. Of these patients, 82 underwent stent-assisted coiling and 46 underwent flow diversion with the Pipeline Embolization Device (PED). Twenty-eight patients (22%) were treated in the setting in subarachnoid haemorrhage. There were only 2 (1.6%) thromboembolic complications and 2 (1.6%) haemorrhagic complications (1 subclinical worsening of the computed tomographic appearance of a subarachnoid haemorrhage and 1 post-PED parietal haemorrhage that was managed conservatively) in the series. The rate of treatment-related permanent morbidity and mortality were only 0.8% and 0%, respectively. Conclusion: The results of this study suggest that a protocol of anticoagulation with a maintenance infusion of tirofiban during stent-assisted coiling and flow diversion of intracranial aneurysms has an excellent safety profile. This protocol provides a reasonable alternative to pre-treating with aspirin and clopidogrel. The protocol is also particularly useful in patients with ruptured aneurysms or when the use of a stent was unexpected. Disclosures: N. Chalouhi: None. M. Zanaty: None. R. Starke: None. P. Jabbour: None. D. Hasan: None.